Design and Simulation of a GSM, Buzzer, and GPS Module-Based Accident Detection System - Muhammad Abubakar Falalu; Ibrahim Umar; Amina Ibrahim; Abdulkadir Shehu Bari; Naja’atu Kabir Naja’atu Kabir; Aminu Aminu; Muhammad Ahmad Baballe (International Journal of Information Systems and Informatics, 2023)
The average number of automobiles on the roads around the world has increased as cars become more and more accessible. Our lives are now easier because to the technology and infrastructure that are developing quickly. Technology has also increased the frequency of traffic risks and road accidents, which result in significant loss of life and property due to inadequate emergency resources. Accidents wreak havoc on victims, costing them valuable time and money. It has been determined via considerable research that the majority of accidents result in fatalities as a result of poor communication with the relevant medical authorities and the ensuing dearth of prompt medical assistance. In this study, an accelerometer can be applied as a rollover or crash detector for the car both during and after a collision. The vibration sensor can also be employed in research to measure the vibration rates of any vehicle. A serious accident can be identified by keeping an eye on the information from the accelerometer and vibration sensor. The police control center, any rescue team, or the owners of the vehicle are then sent the alert message via the GSM module, together with the latitude and longitude information provided by the GPS module. As a result, as soon as they receive the emergency notification, the police can locate the accident's site and take the appropriate action. When an accident occurs in a remote place and no one is available to report it, this technique may prove to be a lifesaver. By responding quickly, the emergency services can prevent an accident from happening and save a life